Status Ontologis Perempuan (Gugutan Riffat Hasan atas Konstruksi Teologis dari Konsep Gender) - Agus Himmawan Utomo (Jurnal Filsafat "WISDOM", 2003)
The phenomena of gender inequalities such as subordination discrimination and violance upon women made up feminist to change the situation conscriously. Riffat Hasan, a moslem feminist, made the effort to reconstruct a minor theological understanding of women in Moslem world's which is supposed to be the roots of gender inequalities. Women aren't created only for completing the life of men as shown in some verses and hadits. Ontological-status of woman is not depend on what, when, and from where they were created